Training the health team with the population in identifying leprosy: An integrative review (Research, Society and Development, 2024)
The study is based on an integrative review that aimed to synthesize scientific knowledge in national and international journals on the training of the health team with the population in identifying leprosy in the Conjunto Vitória neighborhood in Imperatriz. A bibliographical survey was carried out in April 2020 in SciELO and Google Scholar covering publications in medicine, from 2003 to 2020. The study sample comprised 21 articles, among these, 13 were selected after a selection criterion, of which 4 have qualitative and 5 quantitative prevalences. The most studied population was made up of users of Basic Health Units (UBS). It was concluded that research on this topic is focused on the obstacles detected regarding the training of health professionals, who play a vital role in transmitting information about leprosy to the community, with the aim of clarifying patients about the disease and thus facilitating the treatment and detection of sick patients, with due care, reducing the spread of the disease, and promoting the well-being of patients living with the disease.